The Relationship Between Early Marriage and The Incidence of Retained Placenta - Rani Safitri; Sulastri Sulastri; Nila Widya Keswara (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
According to the World Health Organization (WHO), in 2015 the global maternal mortality rate (MMR) reached 303,000 deaths. In Indonesia, the MMR for the same year was 305 maternal deaths per 100,000 live births, significantly higher than the national target of 75 per 100,000 live births. The top five causes of maternal death in Indonesia include hemorrhage (30.3%), hypertension in pregnancy (27.1%), infection (7.3%), prolonged labor (1.8%), and abortion (1.6%). One complication that can contribute to maternal morbidity and mortality is placental retention, a condition in which the placenta fails to be delivered within 30 minutes after childbirth. In 2016, 51 cases of placental retention were reported in the study area, raising concerns about its prevalence and contributing factors. This study aimed to determine the relationship between maternal age and the incidence of placental retention. An analytic survey method was applied using secondary data, with a total population of 398 mothers and a sample of 80 respondents selected through purposive sampling. Data analysis employed chi-square testing. The findings revealed that the majority of respondents were not in the at-risk age group (61 respondents or 76.2%), and most did not experience placental retention (64 respondents or 80%). However, statistical analysis demonstrated a significant relationship between maternal age and placental retention, with a p-value of 0.001, indicating that age is a contributing factor. In conclusion, maternal age plays a significant role in the occurrence of placental retention, emphasizing the importance of adequate maternal health education, early antenatal care, and close monitoring during delivery, especially for those in high-risk age categories. Targeted interventions to address age-related risks may help reduce maternal complications and contribute to lowering the maternal mortality rate.